2015
DOI: 10.1128/aem.01134-15
|View full text |Cite
|
Sign up to set email alerts
|

Genes Associated with Desiccation and Osmotic Stress in Listeria monocytogenes as Revealed by Insertional Mutagenesis

Abstract: Listeria monocytogenes is a foodborne pathogen whose survival in food processing environments may be associated with its tolerance to desiccation. To probe the molecular mechanisms used by this bacterium to adapt to desiccation stress, a transposon library of 11,700 L. monocytogenes mutants was screened, using a microplate assay, for strains displaying increased or decreased desiccation survival (43% relative humidity, 15°C) in tryptic soy broth (TSB). The desiccation phenotypes of selected mutants were subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 110 publications
(115 reference statements)
3
34
0
Order By: Relevance
“…The plates were then stored for 3 days at 20°C in desiccators (SICCO, Bohlender, Germany) pre-conditioned to 33% relative humidity (RH) using a saturated solution of MgCl 2 (protocol adapted from Hingston et al, 2015). The RH of the chambers was monitored throughout the desiccation periods using data loggers (included with desiccators).…”
Section: Methodsmentioning
confidence: 99%
“…The plates were then stored for 3 days at 20°C in desiccators (SICCO, Bohlender, Germany) pre-conditioned to 33% relative humidity (RH) using a saturated solution of MgCl 2 (protocol adapted from Hingston et al, 2015). The RH of the chambers was monitored throughout the desiccation periods using data loggers (included with desiccators).…”
Section: Methodsmentioning
confidence: 99%
“…Also unique to the 6719 hydrogen peroxide response was the upregulation of two oxidative stress protection genes: sodA (LM6179_2184), a superoxide dismutase upregulated by a log2fold change of 0.79, and LM6179_1300, annotated as a glutathione peroxidase and upregulated by a log2fold change of 0.56 (Chatterjee et al, 2006;Hingston et al, 2015). The importance of the superoxide dismutase in L. monocytogenes stress response has been documented before (Soni et al, 2011;Bucur et al, 2018), and upregulation of the EGD-e homolog of LM6179_1300, lmo0983, was observed following exposure to chlorine dioxide (Pleitner et al, 2014).…”
Section: Chromosomal Gene Expression Changes In Response To Hydrogen mentioning
confidence: 99%
“…X14-1, which was isolated from desert soil, encodes proteins for the utilisation of a wide array of carbon substrates, as well as key enzymes for CO 2 fixation that are absent from Pontibacter species isolated from non-xeric environments4 .Many energy-consuming processes, such as flagellar motility and chemotactic machinery26,27,78,85 , are down-regulated in cells under desiccating conditions. Similarly, flagellar motility mutants of the food-borne pathogen L. monocytogenes tolerated desiccation better than wild-type cells90 . Given the energy requirements of flagellar motility, it may become a dispensable function under desiccating conditions, allowing ATP to be redirected to more important metabolic processes90 .…”
mentioning
confidence: 97%
“…Similarly, flagellar motility mutants of the food-borne pathogen L. monocytogenes tolerated desiccation better than wild-type cells90 . Given the energy requirements of flagellar motility, it may become a dispensable function under desiccating conditions, allowing ATP to be redirected to more important metabolic processes90 .…”
mentioning
confidence: 97%